Blue Extinction in Literature, Art, and Culture - Fibisan, Vera.; Murray, Rachel; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
"Marine species are central to the study of extinction, yet-with some notable exceptions-their disappearances have often tended to go unnoticed. This timely and wide-ranging volume should help ensure that extinction in all its forms is seared into the public consciousness; and that it becomes possible to imagine a world in which endangered marine species don't go the same way as their extinct counterparts, sinking before they can be properly accounted for into uncharted ocean depths". Graham Huggan, University of Leeds of UK Blue Extinction in Literature, Culture, and Art examines literary and cultural representations of aquatic biodiversity loss, bringing together critical perspectives from the blue humanities and extinction studies. It demonstrates the affordances, as well as the limitations, of literary and artistic forms in exposing the plight of aquatic organisms, drawing attention to the social, political, and economic structures that are contributing to their destruction. Together, the essays in this collection demonstrate how literature and art can challenge dominant cultural conceptions and lingering misconceptions surrounding aquatic biodiversity loss, offering new ways of relating to species ranging from whales to oysters. Vera Fibisan is an Honorary Researcher at University of Sheffield, UK. She is a practice-based researcher and writer, focusing on bodies of water and marginalia. She has published poetry notably in The Sheffield Anthology (Smith/Doorstop, 2012), CAST: The Poetry Business Book of New Contemporary Poets (Smith/Doorstop, 2014), the Wretched Strangers Anthology (Boiler House Press, 2018) and Voices for Change (2020). She is ASLE-UKI Website and Social Media Officer, and Podcast Co-Host of Green Listening: Discussions in Ecocriticism. Rachel Murray is Lecturer in Literature and the Environment at University of Bristol, UK. She specializes in twentieth-century literature, animal studies, and the environment. She is the author of The Modernist Exoskeleton: Insects, War, Literary Form (2020) and is the editor (with Caroline Hovanec) of "Reading Modernism in the Sixth Extinction" for Modernism/modernity. She has published articles in the Journal of Modern Literature, Humanities, and the Journal of Literature and Science, among other venues. She is currently writing a book about marine life in modern and contemporary poetry, provisionally entitled Marine Attachments. .
Introduction.-Blue Extinction'.-'Amitav Ghosh's Dolphins: Extinction, Figuration and Redemption in The Hungry Tide and Gun Island' .-'The Prospects of Criticism in the Brave New Ocean -- Jackson, Verne, and Toussenel.-'Narwhals for all Seasons -- Representation, Evasion and Absence'.-'"We Will All Be Marine Mammals Soon": Oceanic Intimacy and Extinction from Shakespeare to the Left-to-Die Boat' -- 'Held Together -- Learning Attachment from Oysters' .-'Surreal Seas and Embodied Encounters -- Elizabeth Bishop's Darwinian Poetics' .-'Hydromaterialism and Membrane Logic in Elizabeth-Jane Burnett's Of Sea'.-'A Story of Eight Limbs'.-'Spectral Species in the (Political) Abyss -- From Living Fossils to Presumed Extinctions'.-'Alien Rhythms: Sounding Black Futures from the Ocean Floor'.
Keywords: Literature; Ecocriticism; Animal welfare -- Moral and ethical aspects; Communication in the environmental sciences; Biodiversity; World Literature; Ecocriticism; Animal Ethics; Environmental Communication; Biodiversity